Aspirational Competency Expectations for Public Health Nutritionists in Australia: a Consensus Study - Hughes, R.; Begley, Andrea; Yeatman, H. (Wiley-Blackwell Publishing Asia, 2013)
Aim: To assess consensus among public health nutrition (PHN) workforce development stakeholders on the competencies required for effective PHN practice in the Australian workforce context. Methods: A modified Delphi study involving two iterative survey rounds among an expert panel of 33 Australian PHN workforce development stakeholders. Surveys tested panellist ratings (essential, useful, irrelevant) of a listing of 143 competency elements derived from the literature and existing competency standards, across two survey rounds, with feedback between rounds. An arbitrary consensus cut-off of 67% was applied with <10% change between rounds or 100% agreement interpreted as agreement stability. Results: A total of 109 competency elements from the total list of 143 were rated as essential above the consensus cut-off, representing 76% of the original list. Thirty-three (33) elements were rated as essential by 100% of panellists. Approximately 90% or more of the competency elements tested were retained using the 67% cut-off across nutrition science, nutrition communication, professional communication, capacity building and intervention management competency units. Competency elements rated as essential beyond the consensus cut-off concentrated in the practice competency units of nutrition assessment, monitoring and surveillance, capacity building, and intervention management. Conclusions: The results provide an empirical basis for future nutrition curriculum renewal and workforce development innovations and challenge the assumption that existing dietetic workforce preparation based on meeting entry-level competencies is adequate for community and PHN practice.